The determinants of international equity and bond investment - Roque, Vanda (2016)
The purpose of this research is fourfold. First, to investigate whether the determinants of international equity investment differ between investors with different degrees of information, experience and sophistication. For this purpose, the determinants of international equity investment of institutional and noninstitutional investors from 20 OECD countries, in the period 2001-2009, were analysed and compared. The results show that there are significant differences in the determinants of international equity investment between institutional and noninstitutional investors. Particularly, noninstitutional investors exhibit a more pronounced preference for equities of geographical nearby, contiguous and more transparent countries than institutional investors, suggesting that the effect of information costs and familiarity on international equity investment is stronger for less informed, experienced and sophisticated investors. Moreover, the preference for more developed equity markets and the contrarian behaviour are more severe for noninstitutional investors. Hence, the heterogeneity of institutional and noninstitutional investors in international equity investment is not negligible and therefore should be taken into account. Second, to investigate whether the determinants of international bond investment differ between investors with different degrees of information, experience and sophistication. For this purpose, the determinants of international bond investment of institutional and noninstitutional investors from 20 OECD countries, in the period 2001-2009, were analysed and compared. The results show that there are few significant differences in the determinants of international bond investment between institutional and noninstitutional investors. Particularly, the preference for bonds of more transparent countries and the return chasing behaviour are more pronounced for noninstitutional investors, whereas the preference for bonds with lower risk diversification potential is more pronounced for institutional investors. Hence, not only the results for international bond investment do not allow to support (or reject) the argument that information costs and familiarity are more important for less informed, experienced and sophisticated investors, but also they are contrary to the idea that financial variables, namely return and risk diversification, are more important for more informed, experienced and sophisticated investors. Third, to investigate whether the determinants of international equity investment differ from the determinants of international bond investment. For this purpose, the determinants of both international equity and bond investment of institutional and noninstitutional investors from 20 OECD countries, in the period 2001-2009, were analysed and compared. The results show that, although the effect of information costs on international equity investment tends to be stronger than on international bond investment, the differences between assets are not usually statistically significant, especially when the influence of financial variables is taken into account. Hence, it is not possible to conclude that international equity investment is much more information intensive than international bond investment, as suggested by Gehrig (1993) and Portes, Rey and Oh (2001), among others. Fourth, to investigate whether the flight to quality phenomenon is also observable in international investment and whether the flight to quality phenomenon is more pronounced for more sophisticated than for less sophisticated investors. For this purpose, a two-factor and three-factor ANOVA models, respectively, were applied to the international equity and bond investment of institutional and noninstitutional investors from 20 OECD countries in the period 2001-2009. The results suggest that the flight to quality phenomenon is also observable in international investment, as a change from business cycle of expansion to recession causes investors to significantly decrease the average weight invested in more risky assets (equities) and increase the average weight invested in less risky assets (bonds). The results also show that the variation on the average weight assigned to each type of asset, due to changes in business cycles, is significantly stronger for institutional investors than for noninstitutional investors, thereby suggesting that the flight to quality phenomenon is more pronounced for more sophisticated than for less sophisticated investors.